Management Implications For Food MSMEs In Gorontalo Province - Murtisari, Amelia; Wibowo, Larasati Sukmadewi; Adam, Echan; Arsyad, Karlena; Pertiwi, Saptya Fajar (Universitas Negeri Gorontalo, 2024)
Food MSMEs in this research are businesses that process agricultural commodities into food products that are managed on a micro, small and medium scale. The aim of the research is to determine the management implications of food MSMEs and the differences in management implementation based on food MSME income in Gorontalo Province. This research uses a quantitative descriptive approach with One Way Analysis of Variance test analysis. Data was collected through interviews with food MSMEs in Gorontalo Province. The sampling technique was purposive sampling with the number of respondents being 42 food MSMEs. The research results are: On average, only 26% of food MSMEs in Gorontalo Province have an organizational structure, 67% have financial records, 69% of MSME owners receive incentives from their business, 81% have business license and 52% have halal certification. The implications of the management model for food MSMEs in Gorontalo Province are 40.48% of the implications of management model 1 (applying 2 management indicators). A total of 21.42% have management implications for model 2 (applying 3 management indicators), and 38.10% have management implications for model 3 (applying 4-5 management indicators). Management implications have a significant effect on the household income level of food MSMEs in Gorontalo Province. The average management implication of 4-5 indicators has a higher level of household income.